The quantification and assessment of depression and anxiety in patients with postoperative gastroparesis syndrome - Zheng LJ; Ma JC; Fang D; Wu LG; Gong ZQ; Qi JB; Zhao XD; Du JB; Ma PL (Dove Medical Press, 2018)
Li-juan Zheng,1 Jia-chi Ma,2 Dong Fang,3 Li-gang Wu,4 Zhen-qiang Gong,4 Jian-bo Qi,5 Xiao-dan Zhao,4 Jian-bo Du,4 Pei-lan Ma5 1Department of Gastroenterology, Gansu Province People’s Hospital, Lanzhou, People’s Republic of China; 2Department of General Surgery, Gansu Province People’s Hospital, Lanzhou, People’s Republic of China; 3Department of Vascular Surgery, Gansu Province People’s Hospital, Lanzhou, People’s Republic of China; 4Ningxia Medical University, Yinchuan, Ningxia, People’s Republic of China; 5Gansu University of Traditional Chinese Medicine, Lanzhou, People’s Republic of China Background: This study aimed to analyze the stage-situation depression and anxiety as well as independent influential factors in patients with postsurgical gastroparesis syndrome (PGS)and to provide dependent indications for treatment. Patients and methods: The self-rating depression scale (SDS) and self-rating anxiety scale (SAS) were used to test the depression and anxiety of 53 patients with PGS, who were treated in the Department of Gastroenterological Surgery of Gansu Provincial Hospital from January 2012 to October 2016. A comparison between the SDS or SAS scores of patients with PGS and without PGS was undertaken; then, we retrospectively analyzed the factors influencing depression and anxiety in PGS patients. Results: The patients with PGS’ mean scores of depression and anxiety were 49.92±11.37 and 50.91±6.57, respectively, which were higher than that of patients without PGS in the Chinese population (P<0.05). The results of multivariate logistic regression analysis indicated that the independent influential factors of depression and anxiety in patients with PGS included course of disease, pancreatic juice leakage, preoperative outflow tract obstruction, postoperative abdominal infection, and anastomotic complication (P<0.05). Patients with a disease course longer than 30 days; with pancreatic juice leakage; and who suffered from preoperative outflow tract obstruction, postoperative abdominal infection, and anastomotic complication had higher ratios of depression and anxiety. Conclusion: Depression and anxiety are clearly evident in patients with PGS, and we should pay attention to this phenomenon and provide appropriate treatment. Keywords: postoperative gastroparesis syndrome, depression, anxiety, influential factors